Multi‐Dimensional Topological Fermions in Electrides - Meng, Weizhen; Zhang, Xiaoming; Jiang, Jiayu; Li, Zihan; Liu, Ying; Dai, Xuefang; Liu, Guodong (Advanced Physics Research, 2023)
Topological electrides have attracted extensive attention in various fields, for example, electrocatalysis, spintronics, electron emitters, etc., due to their non‐trivial topological surface states and unique electronic properties. It is well known that topologically protected nontrivial surface states are not broken by external perturbations and further exhibit high carrier mobility and high electron density on some specific surfaces. In addition, electrides usually possess a lower work function due to the presence of approximately loose excess electrons. In this case, topological electrides not only build a bridge between topological materials and electrides, but also couple various excellent properties of these two materials. Since the concept of topological electrides was first proposed, several novel types of topological electrides have been reported in the last few years. Therefore, it is necessary to give a comprehensive review of these topological electrides. In this review, the history of the development of topological electrides and their current status is systematically summarized. In addition, relevant insights into the challenges and opportunities facing topological materials are provided. Electrides are typical electron‐rich materials in which the excess electrons can be stably transferred to multi‐dimensional cavities, namely 0D cage, 1D channel, and 2D interlayer, respectively. Then, the excess electrons form different types of topological fermions near the Fermi level, such as Weyl points, Dirac points, nodal lines, etc.